A formação humanista do profissional técnico em saúde: uma perspectiva do diálogo entre Makiguti e Freire - Tizzano , Valdirene (2010)
The aim of this paper is to investigate the role of the humanistic education in the formation of the professional Health Technician, starting from the dialogue between Freire and Makiguti, which specifies that the political-pedagogic project of Escola Tecnica de Saúde Pública, Prof. Makiguti has its basis on ethical values such as respect, autonomy and responsibility towards life.To make this paper possible, an autobiographical narrative was used, in order to better understand the (self) taught path of the researcher, from where the image of a cherry tree – meaning ressignification of one’s own path – extracted from situations and moments reflected by the narration of the researcher’s own life story.This issue shows itself as a possibility to develop the analogical thinking which triggers the reflection regarding the humanistic education of the health professional. Just like a cherry tree, the principles, paradigms, and the practice of Buddhism are the roots, the trunk and the seeds that spread themselves from India to Brazil and were embraced and lived by Tsunessaburu Makiguti, a humanistic educator who, as Paulo Freire, proposed an educational system that would turn the person into a creative, critic and the main character of their on formation. To consider the student’s life story, their necessities and expectations, their relations, the affection, the worshipping of “being”, instead of “having”, means, to Paulo Freire, the ethic of life on the educational process. The autobiographical narrative, the bibliographical research, the analysis of documents related to the humanistic education which is present on the political-pedagogic project of Escola Tecnica de Saúde Pública, Prof. Makiguti show that the formation, besides being technical, must worship respect, human dignitiy, ethical dimension, dialogue and collective participation and construction. Thus, collective construction, along with technical preparation, contribute to personal and professional achievements, as well as better assistance for the population. Makiguti and Freire complete each other, therefore presenting that a change is both possible and necessary in order to achieve a education that intends to build or re-build a society in which man interacts with technology, rather than being an object of it.